Gallium gradients in Cu(In, Ga)Se2 thin‐film solar cells. (28th March 2014) - Witte, Wolfram; Abou‐Ras, Daniel; Albe, Karsten; Bauer, Gottfried H.; Bertram, Frank; Boit, Christian; Brüggemann, Rudolf; Christen, Jürgen; Dietrich, Jens; Eicke, Axel; Hariskos, Dimitrios; Maiberg, Matthias; et al.
Abstract: The gallium gradient in Cu(In, Ga)Se2 (CIGS) layers, which forms during the two industrially relevant deposition routes, the sequential and co‐evaporation processes, plays a key role in the device performance of CIGS thin‐film modules. In this contribution, we present a comprehensive study on the formation, nature, and consequences of gallium gradients in CIGS solar cells. The formation of gallium gradients is analyzed in real time during a rapid selenization process by in situ X‐ray measurements. In addition, the gallium grading of a CIGS layer grown with an in‐line co‐evaporation process is analyzed by means of depth profiling with mass spectrometry. This gallium gradient of a real solar cell served as input data for device simulations. Depth‐dependent occurrence of lateral inhomogeneities on the µm scale in CIGS deposited by the co‐evaporation process was investigated by highly spatially resolved luminescence measurements on etched CIGS samples, which revealed a dependence of the optical bandgap, the quasi‐Fermi level splitting, transition levels, and the vertical gallium gradient. Transmission electron microscopy analyses of CIGS cross‐sections point to a difference in gallium content in the near surface region of neighboring grains. Migration barriers for a copper‐vacancy‐mediated indium and gallium diffusion in CuInSe2 and CuGaSe2 were calculated using density functional theory. The migration barrier for the InCu antisite in CuGaSe2 is significantly lower compared with the GaCu antisite in CuInSe2, which is in accordance with the experimentally observed Ga gradients in CIGS layers grown by co‐evaporation and selenization processes. Copyright © 2014 John Wiley & Sons, Ltd. Abstract : We present a comprehensive study on the formation, nature, and consequences of gallium gradients in Cu(In, Ga)Se2 (CIGS) solar cells deposited by the sequential and co‐evaporation processes. The formation of gallium gradients is analyzed in real time during a selenization process and gallium gradients of CIGS layers grown by co‐evaporation are analyzed by means of mass spectrometry and served as input for simulations. Depth‐dependent lateral inhomogeneities in CIGS were investigated by luminescence measurements, and migration barriers were calculated using density functional theory.